Aspekte van die spermatologie van die kleinbekgeelvis, Barbus aeneus (Cyprinidae) - Vlok, Wynand (2014)
M.Sc. (Zoology) === Milt and blood samples of Aarbus aeneus were collected during November in order to perform chemical analyses of the blood and seminal plasma. Physical analyses were also carried out on milt. Throughout the year testes were collected in order to determine the stages of testicular development. This was done by means of histological analyses. The sperm counts averaged 8,41 x 10-3 cells rom while the spermatocrit value varied between 44% and 82% (average of 61,9%). All the milt samples collected were white in colour showing a high viscosity. Sperm motility gradually declined after activation and stopped after 82,5 seconds. Chemical values of the components tested in the blood plasma were statistically compared to those in the seminal plasma and no statistically significant differences were recorded between sodium, potassium, chloride, calcium, magnesium, glucose, total lipid, total proteien concentrations, osmolality and pH. The only component where a difference in concentration occured was fructose (30% probability). Sodium, calcium, magnesium, glucose, fructose, total lipid and total proteien concentrations in the blood plasma were significantly lower than the corresponding concentrations in the seminal plasma. In contrast the potassium concentration were higher in the seminal plasma. The pH of the seminal plasma (8,63) was alkaline while a pH of 7,5 was recorded for blood plasma. In the two lobe testis of Barbus aeneus semen is collected with seminiferous ducts into the vas deferens which together with the blood vessels are housed within a hilus. The testis is surrounded by a tunica albugenea and the seminiferous lobules are filled with cysts. The testis of the smallmouth yellowfish appears to be lobular and sperm are deposited into lumens which exist between the cysts. During the resting phase the interstitial tissue is very difficult to distinguish and is seen as a thin layer of cells between the lobules seperating them from one another...